2017
DOI: 10.1590/1806-9061-2017-0585
|View full text |Cite
|
Sign up to set email alerts
|

Body Morphometry and Development of the Digestive System of Grey Partridge (Perdix Perdix) Depending on Age and Gender

Abstract: The experiment used 100 grey partridges (Perdix perdix L.), which were reared first in confinement and later in aviaries. Partridges were lighter and had greater body dimensions at 36 weeks compared to 12 weeks except for trunk length. Older birds showed greater values (p>0.05) of compactness and lower values of massiveness and longleggedness. Significant differences were found for keel length in females. At 36 weeks, male and female partridges had significantly greater total intestinal length, males had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Breast had significantly lower L* value than leg (28.99 VS 30.13) in the current study. In agreement with [14] found lower L* value from breast than from leg, 40.3 and 41.5, respectively. These authors explained that breast had lower L* value than leg which was probably due to the higher fat content in leg than in breast.…”
Section: Colorsupporting
confidence: 90%
See 2 more Smart Citations
“…Breast had significantly lower L* value than leg (28.99 VS 30.13) in the current study. In agreement with [14] found lower L* value from breast than from leg, 40.3 and 41.5, respectively. These authors explained that breast had lower L* value than leg which was probably due to the higher fat content in leg than in breast.…”
Section: Colorsupporting
confidence: 90%
“…Breast had lower a* value than leg might be explained by breast had less myoglobin than leg so breast color was less redness [9]. However, from [13] showed that breast and leg had the same a* value approximately 13.5 and [14] also reported that a* value of breast and leg were 17.8 and 17.7, respectively. Breast and thigh had the same b* value and were higher than from leg and fillet in the present study.…”
Section: Colormentioning
confidence: 99%
See 1 more Smart Citation
“…The body weight of partridges at 8 weeks of age in own studies was similar to the body weight of partridges at the 12 th week of life ascertained by Adamski and Kużniacka (2007). Kokoszyński et al (2017) showed partridges at the age of 12 weeks with an average body weight of 324.2 g (female) to 344.8 g (male). Significantly lower mean body weight of grey partridges in the 3rd and 6th weeks of life, respectively: 38.9-41.6 g and 105.2-110.5 g in their studies, Nowaczewski et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…The carcass weight of each chicken was measured only at the age of 42 days, after slaughter. The gastrointestinal tract, small intestine, caeca, and large intestine lengths were determined using a tape measure (Kokoszyński et al, 2017). The pH of gut contents (crop, proventriculus, gizzard, ileum, caecum, and colon) was measured using a digital pH meter (Crison, Basic 20 pH meter).…”
Section: Data Collectionmentioning
confidence: 99%